COVID-19 vaccination hesitance and adverse effects among US adults: a longitudinal cohort study - Abdelmasseh, M.; Cuaranta, A.; Iqbal, A.; Kadiyala, V.; Willis, J.; Gorka, A.; Thompson, E.; Finley, R.; Payne, B.; Sanabria, J. (Frontiers in Epidemiology, 2024)
Although Coronavirus disease 2019 (COVID-19) vaccination is critical to control its spread, vaccine hesitancy varies significantly among the United States population; moreover, some vaccine recipients experienced various adverse effects. We aim to assess the impact of COVID-19 vaccine hesitancy in a university-affiliated community, the factors affecting participants' decisions, and their adverse effects.A pre-vaccination online Institutional Review Board IRB-approved survey was emailed in Nov/Dec 2020, 2 months before the implementation of state-policy protocols for COVID-19 vaccination. A post-vaccination survey was emailed in May/June 2021, two months after protocol execution. A third follow-up survey was sent in Nov/Dec 2021, and a fourth was sent in June/July 2022. The study population included three groups of adult participants: university students, faculty, and staff-(MS), university health system patients-(MP), and Cancer Center patients-(MCP). The study was designed as a longitudinal cohort study. Statistical analyses were performed using SPSS.With a combined response rate of 26% (40578/157292) among the four surveys, 15,361 participants completed the first survey (MS=4,983, MP=9,551, and MCP=827). 2/3 of participants (63.5%) were willing to get vaccinated, with a significant difference in acceptance among groups, MS:56.6%, MP:66.2%, and MCP:71.6% (p<0.05). Vaccine acceptance rates reached 89% in the second survey after the vaccine's approval, with a lower acceptance rate of MS:84.6% than with MP:90.74% and MCP:92.47% participants (p<0.05). Safety and effectiveness concerns were the main factors affecting participants' decisions in all the first three surveys; however, participants reported these concerns decreased between pre-vaccination, postvaccination, and follow-up surveys with 87%, 56%, and 46%, respectively(p<0.05). More than twothirds of the participants (70%) reported having either minor/moderate symptoms (61.6%) or major symptoms (8.6%) after getting some of the vaccine doses. (p<0.05) CONCLUSION. The hesitance of COVID-19 vaccination was associated with concerns regarding its safety and efficacy. Vaccine acceptance rose higher than expected after protocol execution, likely due to continuous education, whereas safety and efficacy remain factors hindering vaccine acceptance. Continuous education focusing on safety and efficacy of the vaccine can reduce vaccine hesitancy and raise the rates of vaccination.